Ruptured ovarian cyst hemorrhage: the swing between conservative and surgical management - Al-Shukri, Maryam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Ruptured ovarian cyst hemorrhage is one of the causes of acute abdomen in women of reproductive age group that can be life threatening.1 There have been persistent interest in the discussion of managing ruptured ovarian cyst with or without ovulation.1–4 The dilemma of surgical versus conservative/non-surgical management always exist in such cases. It is more of a conundrum when the patient has abnormal coagulation due to either hematological disorders or as a result of anticoagulants.1,5 Commonly, indications for surgical interventions are variable and includes: if the source of the bleeding is not confirmed, if patient is hemodynamically unstable, or if there are evidence of ongoing bleeding not settling despite conservative measures in a reasonable time.1